2017
DOI: 10.1007/s00520-017-3713-9
|View full text |Cite|
|
Sign up to set email alerts
|

Reliability and validity of the Pittsburgh Sleep Quality Index in breast cancer patients

Abstract: The unidimensional construct of the European Portuguese version of the PSQI showed adequate reliability and validity among breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 34 publications
3
50
2
Order By: Relevance
“…The factor analysis of the PSQI has been reported on diverse samples including university/college students in Nigeria, India, Chili, Chinese, Ethiopia, Peru and Thailand, pregnant women, community dwelling adults and older adults in America, Australia, China, Ethiopia, Spain, Portugal, Iranian health professionals, adolescents and young adults [ 15 – 17 , 23 , 24 , 26 – 28 , 31 , 34 , 36 , 39 , 41 , 44 , 45 , 52 , 53 , 57 60 ]. Moreover, it has been reported for patient population with breast cancer, Crohn’s disease, depression, diabetes, women with hot flashes, Taiwanese insomniacs, post-traumatic stress disorder, Trauma exposed veterans, temporo-mandibular disorder, traumatic brain injury, fibromyalgia, arthritis, chronic fatigue syndrome, psychiatric disorders and renal transplant patients [ 25 , 27 , 29 , 30 , 32 , 33 , 35 , 37 , 38 , 40 , 42 , 43 , 46 , 49 , 51 , 61 – 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The factor analysis of the PSQI has been reported on diverse samples including university/college students in Nigeria, India, Chili, Chinese, Ethiopia, Peru and Thailand, pregnant women, community dwelling adults and older adults in America, Australia, China, Ethiopia, Spain, Portugal, Iranian health professionals, adolescents and young adults [ 15 – 17 , 23 , 24 , 26 – 28 , 31 , 34 , 36 , 39 , 41 , 44 , 45 , 52 , 53 , 57 60 ]. Moreover, it has been reported for patient population with breast cancer, Crohn’s disease, depression, diabetes, women with hot flashes, Taiwanese insomniacs, post-traumatic stress disorder, Trauma exposed veterans, temporo-mandibular disorder, traumatic brain injury, fibromyalgia, arthritis, chronic fatigue syndrome, psychiatric disorders and renal transplant patients [ 25 , 27 , 29 , 30 , 32 , 33 , 35 , 37 , 38 , 40 , 42 , 43 , 46 , 49 , 51 , 61 – 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…We counted the number of studies reporting any of the following 5 indices: Kaiser-Meyer-Olkin (KMO) Measure of Sampling Adequacy, Bartlett’s sphericity test, determinant score, anti-image, and component correlations (Table 1 ). Eighteen studies reported both the KMO and Bartlett’s sphericity test [ 15 – 17 , 25 , 39 , 43 45 , 51 53 , 57 59 , 61 , 64 , 65 , 67 ], reported inter-item correlations [ 16 , 22 , 24 , 25 , 27 , 29 , 30 , 32 34 , 36 , 37 , 41 , 42 , 45 , 46 , 50 , 53 , 57 , 64 – 67 ], and 11 studies did not report any index [ 23 , 26 , 28 , 31 , 35 , 38 , 40 , 49 , 60 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of sleep disturbance commonly used self-report instruments to provide a global evaluation of patients' sleep quality (Hanish, Lin-Dyken, & Han, 2017). The Pittsburgh Sleep Quality Index (PSQI) is a well-established measure of sleep disturbance that has been widely applied across a range of cancer populations, including breast cancer (Fontes et al, 2017;Otte, Rand, Carpenter, Russell, & Champion, 2013), lung cancer (Dean et al, 2013) and so on. It is composed of 19 items, yielding a total score that allows researchers to determine sleep dysfunction over a 1-month period (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989).…”
Section: Introductionmentioning
confidence: 99%